Structural issues in the Japanese labor market - An era of variety, equity and efficiency or an era of bipolarization? - Bank of Japan. Institute for Monetary and Economic Studies, Tokyo; Tachibanaki, Toshiaki; Fujiki, Hiroshi; Kurada Nakada, Sachiko (Tokyo, 2000)
"This paper describes several structural changes in the Japanese labor market and related institutional factors with special emphasis on the labor supplies of part-time workers and discouraged workers. We also discuss necessary reforms in the labor market and some implications of such structural changes on the conduct of monetary policy."